Investments in Internet-based Innovations in Financial Services: Advantage or Necessity? - GOH, Kim Huat (Institutional Knowledge at Singapore Management University, 2015)
Information technology (IT) is a key resource for the success of financial services firms. IT plays the role of a driver of innovation and strategic advantage, but also ensures a firm does not suffer strategic disadvantage, and is able to maintain a strong defensive position for its customers and market share. This article presents propositions related to the deployment of internet banking technology innovations among US commercial banks in the 2000s. The goal is to understand what motivated the banks to invest and what the impacts were. The research recognises that some banks may have been in a position to achieve strategic advantage, while others were doing so for more defensive reasons. The emphasis is on managerial interpretation of how to separate strategic advantage versus strategic necessity in the assessment of investment in this area of financial IS and technology innovations, and what was learned as a result.